1997
DOI: 10.1016/s0009-9236(97)90150-8
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus oral bioavailability doubles with coadministration of ketoconazole*

Abstract: Because ketoconazole did not alter hepatic bioavailability and because 10 hours separated administration times of the drugs, it appears that the marked increase in tacrolimus bioavailability can be explained by ketoconazole having a local inhibitory effect on tacrolimus gut metabolism or on intestinal P-glycoprotein activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
168
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(175 citation statements)
references
References 29 publications
7
168
0
Order By: Relevance
“…Two recent studies showed that with contemporary immunosuppressive regimens (tacrolimus, mycophenolate and steroids Ϯ antibody induction) low tacrolimus troughs in the first week post transplant were associated with a greater risk of acute rejection [5,6].To tailor therapy better, multiple clinical factors have been explored to determine their effects on tacrolimus pharmacokinetics. It is generally acknowledged that drug interactions, haematocrit, corticosteroid therapy, days post transplant, and race affect tacrolimus pharmacokinetics [3, [7][8][9][10]. It is also established that the cytochrome P4503A5 (CYP3A5)*1 allele is associated with significantly higher tacrolimus CL and lower systemic exposure [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Two recent studies showed that with contemporary immunosuppressive regimens (tacrolimus, mycophenolate and steroids Ϯ antibody induction) low tacrolimus troughs in the first week post transplant were associated with a greater risk of acute rejection [5,6].To tailor therapy better, multiple clinical factors have been explored to determine their effects on tacrolimus pharmacokinetics. It is generally acknowledged that drug interactions, haematocrit, corticosteroid therapy, days post transplant, and race affect tacrolimus pharmacokinetics [3, [7][8][9][10]. It is also established that the cytochrome P4503A5 (CYP3A5)*1 allele is associated with significantly higher tacrolimus CL and lower systemic exposure [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Corticotherapy may also represent a significant underlying factor, since it uses the same isoenzymes of cytochrome P 450 for byotransformation (CYP3A4), leading to a decrease of tacrolimus level in the blood, having a slight enzymatic inductor effect [15]. Another important element is the age of renal allograft, the patients age at the moment of transplant, the medication administered for other comorbidities such as calcium-channel blockers (felodipine) for the treatment of hypertension -4 patients from group 1 and 2 patients from group 2 [16]; theophylline for the treatment of asthma -1 patient from group 1 [17], ketoconazole, inhibitor of CYP3A4, for the treatment of mycotic infections -2 patients from group 1 and 1 patient from group 2 [18],the patients' diet (grapefruit juice, intake of pomelo, foods that may act as enzymatic inhibitors of CYP3A4) [19,20], CYP3A4 polymorphism [21]. All of the above …”
Section: Discussionmentioning
confidence: 99%
“…It is also advantageous to develop new chemical entities with minimal DDI liabilities, so that package insert ("black box") warnings can be avoided and patient safety maximized as much as possible. The highly publicized market withdrawals of two DDI "victim" drugs, terfenadine and cerivastatin, were precipitated partially because of a drug interaction involving the inhibition of CYP3A4 and CYP2C8, respectively (Honig et al, 1993;Backman et al, 1994;Varhe et al, 1994;Gomez et al, 1995;Floren et al, 1997;Azie et al, 1998;Gorski et al, 1998;Greenblatt et al, 1998;Backman et al, 2002;Emoto et al, 2006). More recently, drug interactions involving the inhibition of tizanidine (CYP1A2-dependent), repaglinide (CYP2C8/CYP3A4-dependent), and fluticasone (CYP3A4-dependent) clearance have also received some attention (Niemi et al, 2003;Arrington-Sanders et al, 2006;Backman et al, 2006).…”
Section: Applicationmentioning
confidence: 99%